2012
DOI: 10.4049/jimmunol.1200804
|View full text |Cite
|
Sign up to set email alerts
|

An Anti-Nucleic Acid Antibody Delivers Antigen to the Cross-Presentation Pathway in Dendritic Cells and Potentiates Therapeutic Antitumor Effects

Abstract: Cross-presentation is important for initiating CTL responses against tumors. Delivery of exogenous Ags to the cross-presentation pathway in dendritic cells (DCs), using a number of different carriers, has been attempted to further understand the mechanisms underlying cross-presentation and to develop therapeutic tumor vaccines. The present study reports a new antigenic carrier molecule: a single-chain V region fragment (scFv) of a nucleic acid–hydrolyzing Ab, 3D8. A fusion protein comprising 3D8 scFv and the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…We reported previously the results of a mutational analysis based on the x-ray crystallographic structure of 3D8 scFv, which showed that the His residues in CDR1 of the heavy chain (HCDR1) and CDR3 of the light chain (LCDR3) are critical for DNA hydrolysis ( 15 ). 3D8 scFv is endocytosed via the caveolae-mediated pathway and localizes to the cytosol without translocating to the nucleus ( 14 , 16 ). Moreover, we found that the activities of 3D8 scFv are relatively tolerant of alteration of the CDR.…”
Section: Introductionmentioning
confidence: 99%
“…We reported previously the results of a mutational analysis based on the x-ray crystallographic structure of 3D8 scFv, which showed that the His residues in CDR1 of the heavy chain (HCDR1) and CDR3 of the light chain (LCDR3) are critical for DNA hydrolysis ( 15 ). 3D8 scFv is endocytosed via the caveolae-mediated pathway and localizes to the cytosol without translocating to the nucleus ( 14 , 16 ). Moreover, we found that the activities of 3D8 scFv are relatively tolerant of alteration of the CDR.…”
Section: Introductionmentioning
confidence: 99%
“…Confocal microscopy revealed that all internalizable 3D8 antibodies localized to the cytosol of THP-1 cells (Figure 2C ). Previous studies report internalization of 3D8 scFv into the cytosol of human epithelial (HeLa) cells, human embryonic kidney (HEK293T) cells ( 19 , 21 ), and mouse dendritic (DC2.4) cells ( 22 ). By contrast, a negative control polyclonal human IgG localized to the cell surface [probably due to capture by Fcγ receptors (FcγRs)].…”
Section: Resultsmentioning
confidence: 99%
“… 19 Antibodies coupled to tumour proteins have been shown to induce CD8 + T cell activation via cross presentation of antibody complexes by mouse DCs. 20 In addition, a cancer vaccine based on coupling tumour antigens such as her-2/neu to an scFv anti-CD19 mAb has been shown to reduce tumour growth. 21 …”
Section: Discussionmentioning
confidence: 99%